2017
DOI: 10.1007/s12298-017-0481-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of bread wheat genotypes in Iran for some nutritional value and baking quality traits

Abstract: Genetic variation among 78 irrigated bread wheat genotypes was studied for their nutritional value and baking quality traits as well as some agronomic traits. The experiment was conducted in a randomized complete block design with three replicates under normal and terminal drought stress conditions in Kermanshah, Iran during 2012-2013 cropping season. The results of combined ANOVA indicated highly significant genotypic differences for all traits. All studied traits except grain yield, hectoliter weight and gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…In crop rotations after preceding crop pea, in 2017 the statistically significant higher falling number was found out (426 s) than in 2016 (400 s) and the year 2018 (404 s) -Table 5, Table 11. These results correlate with those reported by Amiri et al (2018) who argued that the stress due drought resulted in a decreasing grain yield and at the same time an increasing of falling numbers. The results of Eljak et al (2018) indicated, that the falling number of wheat flours was significantly affected by the fertilisation and environmental conditions.…”
Section: Falling Numbersupporting
confidence: 92%
“…In crop rotations after preceding crop pea, in 2017 the statistically significant higher falling number was found out (426 s) than in 2016 (400 s) and the year 2018 (404 s) -Table 5, Table 11. These results correlate with those reported by Amiri et al (2018) who argued that the stress due drought resulted in a decreasing grain yield and at the same time an increasing of falling numbers. The results of Eljak et al (2018) indicated, that the falling number of wheat flours was significantly affected by the fertilisation and environmental conditions.…”
Section: Falling Numbersupporting
confidence: 92%
“…Also TGW, protein content, and gluten content showed a moderate positive phenotypic association with GY. Several studies showed inverse relationship between grain yield and grain N concentration (Triboï et al, 2006; Amiri et al, 2018). They suggested that this inverse relationship is because the genetic variations in C assimilation are higher than those of N assimilation.…”
Section: Discussionmentioning
confidence: 99%
“…Irano žemės ūkio tyrimų, švietimo ir konsultavimo organizacijos 1 Kermanshah žemės ūkio ir gamtos išteklių tyrimų ir švietimo centras, 2 Lorestan žemės ūkio ir gamtos išteklių tyrimų ir švietimo centras, 3 Khorasan Razavi žemės ūkio ir gamtos išteklių tyrimų ir švietimo centras…”
Section: Sėjos Laiko įTaka Duoninių Kviečių Grūdų Kiekybiniams Ir Kokunclassified